Pelatihan Bioteknologi Yoghurt menjadi Produk Usaha Potensial UMKM Desa Borikamase yang Diberdayakan KKN-Tematik IPA UNM - Asriani Asriani; Ramlawati Ramlawati; Muhammad Akbar (JKM: Jurnal Kemitraan Masyarakat, 2023)
This yoghurt biotechnology training activity was carried out with the aim of providing (1) information for the community, especially mothers of UMKM Borikamase Village about yoghurt business opportunities (2) providing overview how to manage milk into yoghurt as potential business product. Evaluation of the knowledge of 14 participants was carried out through filling out questionnaires. The results of the evaluation training activities showed that the average participant response to the yoghurt making process was in the agree (S) category as much 48.42%, 49.20% strongly agreed (SS), and much as 7.10% answered neutral (N). The acceptability of the product is in the very acceptable category with a value range of 8-10, and the attractiveness and opportunity of yoghurt as a business is in a very attractive category with a percentage of 93% of participants interested in developing yoghurt as product for entrepreneurship and as many as 86% of participants wish to build a yoghurt business with the brand name "Be Yoghurt". Thus it was concluded that after the provision of material and simulation of making yoghurt through training, participants could easily understand the process of processing milk into yoghurt starter and then through fermentation technology using yoghurt starter into yoghurt products.